Effect of point of care testing for C reactive protein and training in communication skills on antibiotic use in lower respiratory tract infections: cluster randomised trial. (5th May 2009) - Cals, Jochen W L; Butler, Christopher C; Hopstaken, Rogier M; Hood, Kerenza; Dinant, Geert-Jan
Abstract : Objective To assess the effect of general practitioner testing for C reactive protein (disease approach) and receiving training in enhanced communication skills (illness approach) on antibiotic prescribing for lower respiratory tract infection. Design Pragmatic, 2×2 factorial, cluster randomised controlled trial. Setting 20 general practices in the Netherlands. Participants 40 general practitioners from 20 practices recruited 431 patients with lower respiratory tract infection. Main outcome measures The primary outcome was antibiotic prescribing at the index consultation. Secondary outcomes were antibiotic prescribing during 28 days' follow-up, reconsultation, clinical recovery, and patients' satisfaction and enablement. Interventions General practitioners' use of C reactive protein point of care testing and training in enhanced communication skills separately and combined, and usual care. Results General practitioners in the C reactive protein test group prescribed antibiotics to 31% of patients compared with 53% in the no test group (P=0.02). General practitioners trained in enhanced communication skills prescribed antibiotics to 27% of patients compared with 54% in the no training group (P<0.01). Both interventions showed a statistically significant effect on antibiotic prescribing at any point during the 28 days' follow-up. Clinicians in the combined intervention group prescribed antibiotics to 23% of patients (interaction term was non-significant). Patients' recovery and satisfaction were similar in all study groups. Conclusion Both general practitioners' use of point of care testing for C reactive protein and training in enhanced communication skills significantly reduced antibiotic prescribing for lower respiratory tract infection without compromising patients' recovery and satisfaction with care. A combination of the illness and disease focused approaches may be necessary to achieve the greatest reduction in antibiotic prescribing for this common condition in primary care. Trial registration Current Controlled Trials ISRCTN85154857 .